Photochemical reaction between biphenyl and N(III) in the atmospheric aqueous phase. (January 2017) - Ma, Jianzhong; Zhu, Chengzhu; Lu, Jun; Wang, Tao; Hu, Shuheng; Chen, Tianhu
Abstract: The photochemical reaction between biphenyl (Bp) and N(III) under irradiation at 365 nm UV light was investigated. The results showed that Bp conversion efficiency was strongly influenced by N (III) concentration, Bp initial concentration and pH. Species-specific rate constants determined by reaction of Bp with H2 ONO + ( k 1 ), HONO ( k 2 ) and NO2 − ( k 3 ) were k 1  = (0.058 ± 0.005 L mol −1  s −1 ), k 2  = (0.12 ± 0.06 L mol −1  s −1 ) and k 3  = (0.0019 ± 0.0003 L mol −1  s −1 ), respectively. Laser flash photolysis studies confirmed that OH radical deriving from the photolysis of N(III) attacked aromatic ring to form Bp-OH adduct with a rate constant of 9.4 × 10 9  L mol −1  s −1 . The products analysis suggested that Bp-OH adduct could be nitrated by N (III) and NO2 to generate nitro-compounds. Graphical abstract: Highlights: The rate constants of biphenyl with H2 ONO +, HONO and NO2 − were determined. OH reacts with biphenyl with a rate constant of 9.4 × 10 9  L mol −1  s −1 . Nitro-compounds was generated from the reaction between biphenyl with N(III).